Prevalence of premature ovarian insufficiency and its determinants in Iranian populations: Tehran lipid and glucose study - Marzieh Rostami Dovom; Razieh ‌Bidhendi-Yarandi; Kazem Mohammad; Maryam Farahmand; Fereidoun Azizi; Fahimeh Ramezani Tehrani (BMC, 2021)
Abstract Background Premature ovarian insufficiency (POI) considered as a concerning health issue for women of reproductive age. In this study we aim to estimate the prevalence of POI and assessing the influential factors. Methods Data was obtained from Tehran lipid and glucose study (TLGS). All eligible post-menarcheal female participants of the TLGS, ages 20-65, were recruited (n = 6521). Participants were followed for the event of menopause, and age at menopause was recorded. Kaplan Meier analysis was applied to estimate mean and median for age at menopause. Weibull accelerated failure time survival regression model (AFT), was applied to assess influential determinants of POI. Conditional probability approach was used to provide estimation for prevalence of POI. Results In this population-based study, the prevalence of POI (menopause age < 40 years) and early menopause (menopause age < 45 years) were estimated 3.5% and 24.6%, respectively. AFT model showed that in comparison to normal weight women, time to menopause was decreased by − 0.09 year (95% CI − 0.27, − 0.01, p = 0.023) and − 0.03 year (95% CI − 0.05, − 0.02, p = 0.000) in underweight and overweight women, respectively. Moreover, time to natural menopause was increased by 0.12 year (95% CI 0.07 to 0.17, p = 0.000) in women used oral contraceptives for > 6 months. Conclusion About one quartile of Iranian women experienced menopause at an age less than 45, especially the non-normal weight ones; this high prevalence is a critical public health concerns that needs to be addressed by health policy makers.